First-line gemcitabine plus nab-paclitaxel for elderly patients with metastatic pancreatic cancer: Crossing the frontier of age?. (September 2020) - Vivaldi, Caterina; Salani, Francesca; Rovesti, Giulia; Pecora, Irene; Catanese, Silvia; Casadei-Gardini, Andrea; Massa, Valentina; Bernardini, Laura; Riggi, Laura; Andrikou, Kalliopi; Rapposelli, Giovanni I.; Formica, Vincenzo; et al.
Abstract: Background: Gemcitabine plus nab-paclitaxel (Gem-Nab) represents a standard first-line treatment for metastatic pancreatic cancer (mPC), but few data are available for elderly patients. We aimed to add evidence about safety and efficacy of Gem-Nab in this population. Methods: We collected data of 156 patients with mPC aged ≥65 years receiving Gem-Nab. Patients were stratified according to age: <70 (group 1: 65 patients) and ≥70 years (group 2: 91 patients). Results: The median age was 71 years (range: 65–87 years). The toxicity profile was similar between group 1 and 2, except for all-grade anaemia (92.1% vs . 78.7%, respectively; p = 0.04) and neurotoxicity (61.9% vs . 40.4%, respectively; p = 0.02), also as a result of a lower dose intensity of nab-paclitaxel (83.3% vs . 90.5%, respectively; p = 0.04) administered to oldest patients. The response rate was 25.6% (group 1 vs. 2: 20.0% vs . 29.7%; p = 0.12). After a median follow-up of 26.5 months, median overall survival (OS) and progression-free survival (PFS) were similar between the groups (p > 0.05). The starting dose of Gem-Nab did not affect PFS and OS (p > 0.05). Conclusion: Gem-Nab is active and effective in older patients with mPC, with the results in line with the general mPC population enrolled in clinical trials. Mild dose modifications for elderly patients might be considered to improve safety without impairing efficacy. Highlights: Data regarding first-line chemotherapy in elderly patients with metastatic pancreatic cancer (mPC) are limited. Our aim is to add evidence about safety and efficacy of gemcitabine plus nab-paclitaxel (Gem-Nab) in patients older than 65 years. The results are in line with the general population enrolled in clinical trials. Our data show that Gem-Nab is active and effective in elderly patients bearing mPC.